THE INDONESIAN SPEAKERS TURN SIGNALS IN ENGLISH CONVERSATION:A PRAGMATIC PERSPECTIVE - A. Qashas Rahman (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
One of activities that we, human beings, do in daily life is to have conversations with other members of our family or the society. In order that conversations flow smoothly, involving all the participants, turn signals take place. Turn signals are of various types and are useful to yield, take, or hold a turn. This article reports a research study on the use of turn signals in English conversations by Indonesian speakers in the pragmatic perspective. The results, which are limited to verbal turn signals, showed that Indonesian speakers used four types of turn signals: turn-claiming, turn-yielding, turn-taking, and turn-holding. Depending on the application context, these turn signals can be classified into four pragmatic modes: appropriate and effective, appropriate but ineffective, inappropriate but effective, or inappropriate and ineffective.